2020
DOI: 10.1111/gfs.12475
|View full text |Cite
|
Sign up to set email alerts
|

Millet forage yield and silage quality as affected by water and nitrogen application at different sowing dates

Abstract: This experiment was conducted to evaluate the effects of two irrigation regimes (control and water stress) and two nitrogen (N) levels (0 and 112.5 kg/ha) on forage yield and silage quality in millet. Bastan (Setaria italica (L.) P. Beauv) and Pishahang (Panicum miliaceum) were sown at two different dates during 2015 and 2016. Both cultivars exhibited reduced dry‐matter (DM) yields (45% and 51% in Bastan and Pishahang respectively) due to drought stress. Proline and phenolic contents increased as a result of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
(46 reference statements)
3
6
1
Order By: Relevance
“…Bhattarai et al (2017) and Hassan et al (2020) recognized the effect of soil and air temperature as the determinative factors in germination and yield production in forage sorghum cultivation. Hence Nematpour et al (2020) reported the positive correlation between ADF and DMY, and probably hereupon, in D1 PD , the ambiance condition for growth and development was more desirable, these results recorded. Hassan et al (2019) reported asynchronous growth season and plant development phases would reduce the potential for DMY production.…”
Section: Yield Parameterssupporting
confidence: 53%
See 3 more Smart Citations
“…Bhattarai et al (2017) and Hassan et al (2020) recognized the effect of soil and air temperature as the determinative factors in germination and yield production in forage sorghum cultivation. Hence Nematpour et al (2020) reported the positive correlation between ADF and DMY, and probably hereupon, in D1 PD , the ambiance condition for growth and development was more desirable, these results recorded. Hassan et al (2019) reported asynchronous growth season and plant development phases would reduce the potential for DMY production.…”
Section: Yield Parameterssupporting
confidence: 53%
“…Probably hence in D1 PD , the ambient factors like minimum air temperature and the mean soil temperature stimulated the effect of long days on photosynthesis, subsequently, the level of WSC was higher than other PDs. Nematpour et al (2020) reported forages that planted at the later dates produced higher net energy content for lactation.…”
Section: Yield Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…2,4 Ahrar et al 16 reported that drought stress reduced amaranth forage yield but increased its protein content. Nematpour et al 25 also reported that reduced irrigation water improved some of the forage quality components of millet, including leaf/stem ratio, digestible dry matter (DDM), relative feed value (RFV), and net energy for lactation (NEL).…”
Section: Introductionmentioning
confidence: 99%